2017
DOI: 10.1002/jbm.a.36292
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of rifampin in a polymeric layer‐by‐layer structure for drug delivery

Abstract: Rifampin (RIF) is a bactericidal antibiotic drug and potent inducer of hepatic and intestinal cytochrome P-450 (CYP-450) enzyme systems. Given by mouth or intravenously, it can cause numerous clinical drug interactions; thus, alternative systems of drug delivery that bypass some or all of its toxic effects are well worth investigating. In this study, a controlled layer-by-layer (LBL) process of encapsulating RIF in biocompatible alginate and chitosan polymers loaded onto Fe O nanoparticles was developed. Fe O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…These authors investigated Cytochrome P-450 3A CYP3A) enzymes RIF primarily in the liver and it found that toxicity inducted the cytochrome P 450 (RIF), which is used to increase drug metabolism. Recently, FAs have been used to control RIF release for regulating degradation in the stomach (Esmaeili and Khodaei 2018). Olive oil is a powerful antioxidant due to its unsaturated acids which have properties that can reduce free radicals in the human body (Greiner and Bäckhed 2011;Jeyaraman et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These authors investigated Cytochrome P-450 3A CYP3A) enzymes RIF primarily in the liver and it found that toxicity inducted the cytochrome P 450 (RIF), which is used to increase drug metabolism. Recently, FAs have been used to control RIF release for regulating degradation in the stomach (Esmaeili and Khodaei 2018). Olive oil is a powerful antioxidant due to its unsaturated acids which have properties that can reduce free radicals in the human body (Greiner and Bäckhed 2011;Jeyaraman et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In general, the limit of the suspension’s stability and instability can be determined in terms of zeta potential. Esmaeili and Khodaei 31 reported the negative ZPS of PU. They showed PU can be used as a conductive solution in the double-needled electrospinning method.…”
Section: Resultsmentioning
confidence: 99%
“…The tendency of particles to repel each other is directly related to the zeta potential. In general, the limit of the suspension's stability and instability can be determined in terms of zeta potential.Show more Esmaeili and Khodaei [25] reported the negative ZPS of PU. They showed PU can be used as a conductive solution in the double-needled electrospinning method.…”
Section: Zps Analysismentioning
confidence: 98%